2007
DOI: 10.1017/s0014479707005029
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL N2 FIXATION AND MINERAL N IN COMMON BEAN–MAIZE INTERCROPPING OR SOLE CROPPING IN SOUTHEASTERN BRAZIL

Abstract: The aim of this work was to assess the effects of N levels and intercropping of two common bean (Phaseolus vulgaris) varieties (Carioca and Rio Tibagi) with maize (Zea mays) on accumulated N, grain yield and biomass of both crops, and nodulation of common bean inoculated or not with Rhizobium. Two field experiments were conducted simultaneously: common bean-maize intercropping and common bean in sole cropping. Intercropping increased common bean nodulation and biomass, mainly with Rhizobium, but mineral N was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 15 publications
7
31
1
1
Order By: Relevance
“…Thus, MC alternating ridges pattern achieved the most efficient response in increasing the maize grain yield with progressive N increases, referring to the high-yield benefit of each nitrogen fertilizer unit. This is in accordance with that reported by Cardoso et al (2007), where each kilogram of N applied resulted in 32 and 48 kg of maize grains in sole cropping and in intercropping, respectively. R 2 value showed that the response to N level under MC alternating ridges was more evident in exhibiting changes in the maize yield than under MC same ridge or sole-M.…”
Section: Regression Analysissupporting
confidence: 93%
“…Thus, MC alternating ridges pattern achieved the most efficient response in increasing the maize grain yield with progressive N increases, referring to the high-yield benefit of each nitrogen fertilizer unit. This is in accordance with that reported by Cardoso et al (2007), where each kilogram of N applied resulted in 32 and 48 kg of maize grains in sole cropping and in intercropping, respectively. R 2 value showed that the response to N level under MC alternating ridges was more evident in exhibiting changes in the maize yield than under MC same ridge or sole-M.…”
Section: Regression Analysissupporting
confidence: 93%
“…Many other factors including improved crop management may also contribute to a favorable outcome. Moreover, several reports demonstrated that significant improvement of yield and yield components in common bean was due to N2 fixation [9,32,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Beans, maize, and squash are often cultivated together in traditional cropping systems in Mexico (e.g., milpa cropping system) and other countries of Latin America and in eastern Africa because they complement each other agronomically (e.g., plant nitrogen balance; Cardoso et al, 2007) and nutritionally (e.g., balance of essential amino acids; Bressani, 1983). The actual area of domestication of these crops within Mexico—and particularly, whether these domestications can be traced back to a single region—is still the subject of both archaeological and genetic research.…”
mentioning
confidence: 99%